Perceived organizational support and job satisfaction: A moderated mediation model of proactive personality and psychological empowerment - Annum Tariq Maan; Ghulam Abid; Tahira Hassan Butt; Fouzia Ashfaq; Saira Ahmed (Future Business Journal, 2020)
Drawing on social exchange theory, the purpose of this study is to examine the mediating role of psychological empowerment and moderating role of proactive personality in the relationship between POS and job satisfaction. The data were collected from 936 employees working in various manufacturing and service sectors by using self-report survey questionnaires by employing time-lagged cross-sectional study design. The study findings demonstrate that POS positively influenced psychological empowerment and job satisfaction. Moreover, it is also revealed that the relationship between POS and job satisfaction is weaker when employees' proactive personality is higher rather than lower. The findings of the current study pose a framework for organizational representatives of both service and manufacturing industries to strengthen individual psychological empowerment and job satisfaction by offering organizational support to those individuals who are less proactive.
Keywords: 650; Perceived organizational support (POS); Social exchange theory; Job satisfaction; Psychological empowerment; Proactive personality